Synthetic strategies of phosphonodepsipeptides - Xu, Jiaxi (Beilstein Journal of Organic Chemistry, 2021)
Phosphonodepsipeptides are phosphorus analogues of depsipeptides and phosphonate-linked analogues of naturally occurring peptides. They are more stable than phosphonopeptides and have been widely applied as enzyme inhibitors, haptens for the production of antibodies, biological agents, and prodrugs. The synthetic strategies towards phosphonodepsipeptides are reviewed, including the phosphonylation of hydroxy esters with phosphonochloridates, the condensation of phosphonic monoesters and hydroxy esters, the alkylation of phosphonic monoesters with 1-(alkoxycarbonyl)alkyl halides or sulfonates, multicomponent condensation of amides, aldehydes, and dichlorophosphites followed by alcoholysis with hydroxy esters, the phosphinylation of hydroxy esters with phosphonochloridites followed by oxidation, and the carbene insertion of N-protected amino acids with 1-diazoalkylphosphonates. This review includes the synthesis of α-, β-, and γ-phosphonodepsipeptides and phosphonodepsipeptides with C-1-hydroxyalkylphosphonic acids.
Keywords: alkylation; mimetic; multicomponent condensation; peptide; phosphonopeptide; phosphonodepsipeptide; phosphonylation